174k views
4 votes
Select the correct answer from each drop-down menu.Consider this polynomial equation.6(x – 3)(x^2 + 4)(x + 1) = 0Use the equation to complete this statement.The equation hassolutions. Its real solutions are I

User Tbolender
by
5.0k points

1 Answer

4 votes

ANSWER:

The equation has 4 solutions.

Its real solutions are x =3 and x = 1

Step-by-step explanation:

Given:


6(x-3)(x^2+4)(x+1)=0

To find how many solutions the equation has, we have:

The solution will be the values of x.

There are factors already, which are:

(x - 3) = 0

x² + 4 = 0

x + 1 = 0

Therefore, the solutions are:

x = 3

User Patrick Tescher
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.